2019
DOI: 10.1021/acs.inorgchem.8b03223
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Strength of Photophysical Measurements for in Vitro Photobiological Activity in a Series of Ru(II) Polypyridyl Complexes Derived from π-Extended Ligands

Abstract: This study investigates the correlation between photocytotoxicity and the prolonged excited state lifetimes exhibited by certain Ru(II) polypyridyl photosensitizers comprised of π-expansive ligands. The eight metal complexes selected for this study differ markedly in their triplet state configurations and lifetimes. Human melanoma SKMEL28 and human leukemia HL60 cells were used as in vitro models to test photocytotoxicity induced by the compounds when activated by either broadband visible or monochromatic red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

7
2

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 90 publications
(134 reference statements)
2
38
0
Order By: Relevance
“…Next, the singlet oxygen quantum yields for Ru(II) complexes 1 ‐ 7 were measured. Table shows that the Φ ∆ values ranged from a high of 0.87 for 6 to a low of 0.58 for 1 , which compare favorably to literature values for 8 (0.17) , 9 (0.79) , 10 (0.78) and 11 (0.74) . For the new Ru(II) complexes, interestingly, we found that the quantum yields increase in the order 1 ≈ 2 ≈ 3 < 4 ≈ 5 < 6 ≈ 7 and very roughly correlate with the decrease of the triplet energies ( E T ) of the π group (R 1 –R 7 ) alone.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Next, the singlet oxygen quantum yields for Ru(II) complexes 1 ‐ 7 were measured. Table shows that the Φ ∆ values ranged from a high of 0.87 for 6 to a low of 0.58 for 1 , which compare favorably to literature values for 8 (0.17) , 9 (0.79) , 10 (0.78) and 11 (0.74) . For the new Ru(II) complexes, interestingly, we found that the quantum yields increase in the order 1 ≈ 2 ≈ 3 < 4 ≈ 5 < 6 ≈ 7 and very roughly correlate with the decrease of the triplet energies ( E T ) of the π group (R 1 –R 7 ) alone.…”
Section: Resultssupporting
confidence: 82%
“…The 1 O 2 produced is detected by its reaction with 9,10-anthracene dipropionate dianion 12 to reach endoperoxide 13. We believe there is value in comparing the new Ru(II) complexes 1-7 to several Ru(II) complexes reported in the literature (31,32). However, we note that such a comparison of EC50 values in the literature run by another group using a different assay procedure is challenging.…”
Section: Synthesis and Characterizationmentioning
confidence: 88%
“…Light‐treated plates were sealed (polyolefin silicone‐adhesive qPCR; VWR, 89134‐428) in the hypoxic atmosphere, moved to normoxia, and illuminated on the benchtop—as described for the normoxia‐treated plates. A reference PS, [Ru(bpy) 2 (dppn)]Cl 2 (Φ Δ = 0.75 in MeCN) , was used due to its absolute dependence on molecular O 2 for photocytotoxicity in the tested cell line, SK‐MEL‐28. The lack of cell kill by this reference PS, observed under microscopy and by resazurin cell‐viability assays, confirmed sufficient hypoxia.Hypoxia interferes with the ability of the resazurin indicator to reliably report on cell viability.…”
Section: Methodsmentioning
confidence: 99%
“…Pure 3 IL states that are lower in energy than the lowest lying 3 MLCT state(s) tend to possess exceptionally long lifetimes (>20 ms) and proved very effective for in vitro PDT. 26,47,[49][50][51][52] From our extensive work in this area, we have found that organic triplets having charge transfer character ( 3 ILCT) contributed by a-oligothienyl groups in certain systems are particularly photoreactive and make excellent PDT agents. 16,48,[53][54][55][56][57][58][59][60][61] Our TLD1433 is one example, which is a bisheteroleptic Ru(II) complex based on the a-terthienylappended imidazo [4,5-f] [1,10]phenanthroline (IP-3T) ligand that generates 1 O 2 with almost unity efficiency.…”
Section: Introductionmentioning
confidence: 99%